PENERAPAN PEMBELAJARAN KOOPERATIF METODE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR TEMBAKAN BEBAS (FREE THROW) PADA SISWA KELAS X-5 SISWA SMA KRISTEN PETRA 3 SURABAYA - Surjadi Hendra; Anung Priambodo (Arena, 2010)
Physical education, sport and health is one of the subjects that are given to students. One of the sports games that are in these subjects is basketball. One of the basic techniques of basketball should have shot the student is free (throw free). Teachers teaching in applying free shot (free throw) difficulties and obstacles and barriers due to lack of knowledge of students in basic techniques of basketball games especially the basic technique of free throw. During this learning model that is used more reference to "teacher center" a lot of lectures and demonstrations using centralized so that in practice often only certain students are mastering the material, and there is a possibility some students less blatant, so skills can not be controlled optimally. It is known from low student test in conducting free shot (free throw) Student Team Achievement Division (STAD) is one of the cooperative learning method is simple and aims to improve learning outcomes through group cooperation. This kind of research using action research class (PTK) which is a cycle including the planning phase, the implementation action, observation and reflection. This research was conducted for two cycles. As before the implementation of the learning method STAD students who meet the criteria of doing well on the category of free shots once only seven people from 32 students or 21%, but after the STAD method implemented there is an increasing number of students who meet the good and excellent categories to 29 people or 91% . Besides the application of the learning method STAD also enhance teamwork and responsibility of each individual so that they help to improve individual scores that ultimately enhance appreciation (recognition) team.